1994
DOI: 10.1203/00006450-199404000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Effects on Growth Are Altered in Rats by Prednisolone and Methotrexate

Abstract: ABSTRACT. CNS therapy for childhood leukemia has adverse effects upon growth and cognition. The cause of these deficits is unknown. In a rat model, we determined which agent, or combination of agents, in CNS therapy affected growth. Young Sprague-Dawley rats were exposed to cranial irradiation (1000 cGy), methotrexate (2 or 4 mg[ kg, intraperitoneally), or prednisolone (18 or 36 mg[kg, intraperitoneally) alone or in two-or three-agent combinations. Matched control groups received appropriate sham radiation, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 21 publications
1
7
1
Order By: Relevance
“…This is probably associated with the poorer growth of body dimensions observed in the same animal group and with the possible testicular toxicity of the treatment. The present observation that female rats do catch-up better than males is supported by the earlier results of SCHUNIOR et al (34), where the body weight of the rats following a single injection of MTX at the age of 18 d returned to control levels by day 80, females recovering sooner than males.…”
Section: Discussionsupporting
confidence: 90%
“…This is probably associated with the poorer growth of body dimensions observed in the same animal group and with the possible testicular toxicity of the treatment. The present observation that female rats do catch-up better than males is supported by the earlier results of SCHUNIOR et al (34), where the body weight of the rats following a single injection of MTX at the age of 18 d returned to control levels by day 80, females recovering sooner than males.…”
Section: Discussionsupporting
confidence: 90%
“…A significant proportion of patients with radiation-induced GH deficiency and disturbances in GH pulsatility (Spoudeas et al 1996) can release GH in response to an acute bolus of GH secretagogues (Ogilvy-Stuart et al 1994); they may be candidates for chronic GHRH analogue treatment to build up their pituitary GH reserve (Ogilvy-Stuart et al 1997, Achermann et al 1999. Schunior et al (1994) used a rodent model of irradiation-induced stunting to evaluate the impact of prior methotrexate or prednisone treatments, and Winterer et al (1988) showed that the radiosensitivity of the GnRH/gonadotroph axis in rodents could be altered by concurrent treatment with GnRH analogues. We hope to use our rodent model to test specific interventions with hypophysiotrophic factors that might prevent or reduce the occurrence, delay the progression, or ameliorate the severity, of long-term multiple endocrine deficits caused by cranial irradiation.…”
mentioning
confidence: 99%
“…58 -60 Proton beam radiation can reduce radiation doses to chiasm, pituitary gland, and noninvolved tissues, with high conformity to target volumes, steep dose gradients, and sparing of normal tissue. 61 Potential interventions to decrease radiation injury include gonadotropin-releasing hormone agonists, 62 prednisone, 63 and lithium. 64 Radiation sensitizers permit lower radiation doses but, alternatively, may produce greater late effects.…”
Section: Interventions To Decrease Injurymentioning
confidence: 99%